College members profile from Campus VIII of the State University of Paraíba: Teaching, research and extension (Research, Society and Development, 2020)
The inseparable triad teaching, research and extension make up the pillars of the Brazilian university. The aim of this work was to evaluate the college members profile of State University of Paraiba (UEPB) Campus VIII. For this, extension and research notices were consulted, and also the curricula lattes from professors of Dentistry, Civil Engineering and Physics courses from Campus VIII. It was verified that the college members staff is composed by a minority of professors. They are mostly men, and are quite engaged in teaching, research and extension, and also in scientific dissemination of their work. Professors preferred to participate in extension projects, with a higher average of projects/professor (n=7.1 projects) in the Dentistry course. In relation to research, a higher average of projects was observed per professor (n=5.5 projects) in the Physics course. The scientific dissemination of Campus VIII is still deficient, with Dentistry professors presenting a higher prevalence of complete articles published in periodics, however, with low impact. Civil Engineering professors presented more papers published in annals of congresses, in relation to other courses, and physics professors are proportionally more connected to teaching in postgraduate courses. Despite being a recent Campus, there is still the need to open public notices to fill the great lack of the effective staff, mainly in Dentistry course from Campus VIII of UEPB.